Organic Reactions 2004
DOI: 10.1002/0471264180.or064.03
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Organochromium Reagents to Carbonyl Compounds

Abstract: Organochromium compounds can be prepared by two methods: (1) transmetallation from the corresponding organolithium, ‐magnesium, or –zinc compounds with chromium(III) halides, and (2) reduction of organic substrates, such as halides and unsaturated compounds with chromium(II) salts. The second method is usually the one ised because the first method suffers from low solubility of chromium(III) salts in ethereal solvents and from the difficulty of preparing organolithium compounds. Low‐valent chromium species are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 650 publications
0
24
0
Order By: Relevance
“…An example is represented by the allylation under Nozaki–Hiyama–Kishi/Fürstner conditions, which combines catalytic amounts of CrCl 2 (or CrCl 3 ) and superstoichiometric amounts of Mn. [201] Although catalytic in the metal that carries out the allylation reaction itself, protocols of this kind are de facto not catalytic, because a stoichiometric amount of metal reducing agent is still required. Truly catalytic methods include the transfer hydrogenation approach described by Krische.…”
Section: The Water-gas Shift Reaction In Organic Synthesismentioning
confidence: 99%
“…An example is represented by the allylation under Nozaki–Hiyama–Kishi/Fürstner conditions, which combines catalytic amounts of CrCl 2 (or CrCl 3 ) and superstoichiometric amounts of Mn. [201] Although catalytic in the metal that carries out the allylation reaction itself, protocols of this kind are de facto not catalytic, because a stoichiometric amount of metal reducing agent is still required. Truly catalytic methods include the transfer hydrogenation approach described by Krische.…”
Section: The Water-gas Shift Reaction In Organic Synthesismentioning
confidence: 99%
“…310 A marked advantage of this carbonyl olefination over the McMurry coupling is that the chromium reagents show high chemoselectivity toward aldehydes, and can be carried out in the presence of keto and ester functionalities.…”
Section: Scheme 27mentioning
confidence: 99%
“…To tell the truth, I did not think at that time that the result of the reaction would initiate a new field of organochromium reagents and result in a review in Organic Reactions. 13 Further experiments revealed that reduction of alkenyl and aryl iodides (or bromides) to alkenyl-and arylchromium reagents with chromium(II) chloride and subsequent Barbiertype carbonyl addition proceeded smoothly. The reaction occurred in a stereoselective manner.…”
mentioning
confidence: 99%
“…13,32,34 1.3 Geminal Dimetallic Reagents for Olefination of Carbonyl Groups: Organotitanium Reagents.…”
mentioning
confidence: 99%
See 1 more Smart Citation